2022
DOI: 10.53621/jider.v2i3.130
|View full text |Cite
|
Sign up to set email alerts
|

Model Pembelajaran Kooperatif Type Index Card Match Terhadap Hasil Belajar IPA Kelas IV SD

Abstract: Penelitian ini bertujuan untuk mengetahui adanya pengaruh hasil belajar IPA dengan menggunakan model pembelajaran kooperatif type Index Card Match pada siswa kelas IV SDN Jatiwaringin III Pondok Gede pada semester 2 tahun ajaran 2018-2019. Metode penelitian yang digunakan adalah metode kuantitatif dengan desain penelitian Posttest-Only Control Design. Sampling yang digunakan pada penelitian ini adalah teknik sampling Non Probability sampling yaitu sampling jenuh. Pada uji validitas dengan menggunakan Korelasi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This learning model directs students to be more active and participate in learning activities while the teacher becomes a facilitator and motivator. This learning process is more interesting because students discuss finding partners in groups while learning about a concept or topic in a fun atmosphere, such as learning while playing the Model Index Card Match (Wahyuningtyas & Zulherman, 2022;Wijanarko, 2017a). This allows students to learn actively and have an independent spirit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This learning model directs students to be more active and participate in learning activities while the teacher becomes a facilitator and motivator. This learning process is more interesting because students discuss finding partners in groups while learning about a concept or topic in a fun atmosphere, such as learning while playing the Model Index Card Match (Wahyuningtyas & Zulherman, 2022;Wijanarko, 2017a). This allows students to learn actively and have an independent spirit.…”
Section: Introductionmentioning
confidence: 99%
“…This cooperative learning model can be applied in the learning process to improve the students' science knowledge competence. Other research showed that the influence of the Index Card Match type Cooperative learning model in improving the learning outcomes (Annisa & Marlina, 2019;Prabowo et al, 2020;Wahyuningtyas & Zulherman, 2022).…”
Section: Introductionmentioning
confidence: 99%